Effect of phototherapy on serum calcium level in term newborns - Ignatious Rozario, Cyril; S. Pillai, Preethi; T., Ranamol (International Journal of Contemporary Pediatrics, 2017)
Background: Hyperbilirubinemia is one of the most prevalent problems in neonates. Jaundice is observed during first week of life in approximately 60% of term neonates and 80 % of preterm neonates. Phototherapy is one of the routine methods for management of hyperbilirubinemia. The aim of this study is to assess the effect of phototherapy on serum calcium level in term newborns with neonatal hyperbilirubinemia who undergo phototherapy and to find out the association between effect of phototherapy on serum calcium level and birth weight, postnatalage, type of feeding and blood group incompatibility. Methods: 100 newborns with neonatal hyperbilirubinemia admitted in newborn nursery were selected for the study. Serum calcium estimation was done before phototherapy. All newborns were subjected to double surface phototherapy. After 48 hours of phototherapy serum calcium was estimated and compared with earlier value. Results: Out of 100 newborns studied 67 babies had a decrease in serum calcium level after 48 hrs of phototherapy. And this reduction in calcium level was found to be statistically significant (p value <0.001). Only 3 babies developed hypocalcemia (serum calcium <7 mg/dl). None of them were symptomatic. There was no significant association between reduction in serum calcium level and birth weight, postnatalage, type of feeding and blood group incompatability. Conclusions: There is signiticant reduction in serum calcium level after phototherapy but risk of hypocalcemia is low in healthy full-term neonates. No significant association was found between reduction in serum calcium level and birth weight, postnatal age,type of feed, and blood group incompatibility.